Analisis Walking Permeability, Walking Effort, dan Walkability Index, Studi Kasus Pada Jalan Braga Bandung - Stephanie Natali Putriana; Besya Fairdian, R. D. A.; Asyraf, Ammar (Jurnal Teknik Sipil, 2024)
Abstract Human movement in Bandung is unavoidable, with traffic congestion and travel distance making walking a popular alternative. Ease of reaching a location is linked to walking distance and time, and route characteristics affect walking effort and accessibility. Jalan Braga is a high pedestrian area in Bandung. This study assesses walkability to Jalan Braga using Walking permeability, Walking Effort, and Walkability Index methods. Results show the highest walkability permeability values for distance and time are 1.81 on Route 4: Naripan Gas Station and 2.29 on Route 6: Bandung City Square. The highest walking effort value is 4362.50 on Route 6: Bandung City Square. The best and worst walkability index values are for Route 6: Bandung City Square and Route 3: Lautze 2 Mosque, respectively.